The Impact of Exposure to Online Mass Media on People's Attitudes in Marriage Decisions in Indonesia - Tazkia Aulia Rahman; Vera Wijayanti Sutjipto; K.Y.S Putri (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
The decline in the marriage rate in Indonesia in the last decade is a complex phenomenon with many interrelated causes. The institution of marriage, once a strong tradition binding two individuals in a commitment to live together, has undergone significant changes in recent decades. The latest data from the Central Statistics Agency (BPS) shows a decreasing trend in the marriage rate nationally. In 2023, there will only be 1,577,255 marriages recorded in Indonesia, a decrease of 128,000 from the previous year. During the last decade, the marriage rate experienced a significant decline of 28.63 percent. In-depth research highlights the socio-economic factors, changes in mentality, and the influence of online mass media, especially social media, that play a role in this change. The influence of online mass media, particularly social media, is also a factor that cannot be ignored in understanding changing attitudes towards the institution of marriage. Social media has broadened access to information and facilitated communication between individuals in unprecedented ways. Not only does this change the way individuals interact and form relationships, but it also influences perceptions of traditional values such as marriage.